PENGARUH PENAMBAHAN DAUN ANTIMIKROBA DAN MODIFIKASI PENYIMPANAN TERHADAP ORGANOLEPTIK LEMANG DALAM MEMPERTAHANKAN UMUR SIMPAN - Melati Pratama; Arief Marna Sonjaya (Fakultas Pertanian Universitas Alkhairaat Palu, 2022)
Lemang is one of malay culinary that was served at ceremonies, eid and etc. Lemang was made from glutinous rice and coconut milk. It was grilled on embers, but it was very easy deterioration. Antimicroba leaves and bamboo storage position was one of experiment to make lemang be survive, but antimicroba leaves had its own characteristics like color, taste, and texture. So, the object of this research was analyze effect antimicroba leaves addition (Pandanus amayllifolius Roxb, Syzygium samarangense and Mangifera indica) and storage modification (normal position and flipped position) to characteristic of lemang organoleptic characteristic. The characteristic of lemang organoleptic was tested by organoleptic test for 30 panelists. The panelists gave score 1 if they dislike, scored 2 if they feel usual, and scored 3 if they feel very like for 7 days. The scored was calculated by Analysis sidik ragam and Beda Nyata Terkecil. The result showed that all treatment gave real effect to aroma, texture and taste to lemang. The all of lemang in normal storage position treatment had dislike scores at the 3rd day. While lemang in flipped storage position treatment had dislike score at the 5th day. The best leaves that for addition lemang processing was Pandanus amayllifolius Roxb. It gave stable aroma, texture and dark color for lemang